The Impact of Public Spending on Imports in Algeria. Econometric Study Between the Period (1990 a 2012) (Global Journal of Management and Business Research, 2015)
We consider public spending as a very important tool in the financial policy and participate essentially in imports. So, there are many studies related to public spending and import. The work below is an application of Co-integration analysis (test of constant variables (augmented Dickey-Fuller) and the test of (Johansen and Juselius). In addition to a corrections sample and the annual report of the period between 1990 -2012. The aim is to study the impact of public spending on import in Algeria.
Keywords: public spending; importation; test of constant variables; correction of mistakes